Towards the 'Third Revolution in Military Affairs': The Russian Military's Use of AI-Enabled Cyber Warfare. Issue 3 (15th April 2020) - Thornton, Rod; Miron, Marina
Abstract : There is an ongoing international arms race in the field of artificial intelligence (AI). But whereas military organisations in the West are viewing AI principally as an enabler in the tactical realm, this is not the case in Russia. The Russian military sees AI's greatest utility at the strategic level. Its emphasis is on employing AI-enhanced information warfare tools (including in cyber warfare) to produce truly game-changing strategic effects against state adversaries. AI's use in this capacity heralds a 'third revolution in military affairs'. Rod Thornton and Marina Miron examine its profound implications for the future of warfare.■